Labisia pumila loaded flexible liposomes for enhancement of collagen synthesis in reconstructed human skin and its penetration pathway - Roslan, Nur Zatul Iradah (2019)
Labisia pumila (LP) contains high antioxidants and has been shown to enhance collagen synthesis in the skin. Thus, LP is suitable to be incorporated in skin care formulations. Flexible liposomes (FL) can be utilized to enhance active ingredients permeation through the skin as they can squeeze through the pores or intercellular junctions of the stratum corneum. This study focused on the development of FL loaded with LP extract for controlled and localized delivery through transdermal route. The formulation of FL-LP was developed using quality by design concept to obtain a comprehensive understanding of the product and process parameters in order to achieve consistent product performance. FL-LP was prepared using thin-film hydration method followed by ultrasonication and the following optimum formulation and process parameter obtained were; 10.43 mg/ml of L- a – phosphatidylcholine, 2.03 mg/ml of ß-sitosterol, 0.16 % v/v of Tween 80 and 0.19 % v/v of Span 80. The optimum time of sonication was three minutes at 30 % amplitude. Stability study indicated that the formulation was stable at 4 °C and no significant changes in physical characterization were observed throughout three months of storage. The release kinetics of the FL-LP was analysed in vitro and it was found to follow the Higuchi model. Transport properties study showed that the permeability coefficient of FL-LP through rat skin and reconstructed human skin were 1.73 ± 0.4 cm/h and 2.53 ± 0.07 cm/h, respectively. The transdermal penetration pathway of FL-LP was further characterized using Confocal Laser Scanning Microscopy. The pathway of penetration of flexible liposomes was mostly through the hair follicles. The correlation of kinetic release study and permeability study was statistically significant, with R2 of 0.9024. The amounts of effective transdermal dosage for collagen synthesis assay of non – encapsulated LP extract and FL- LP were estimated based on safe dosage from IC50 result. Collagen synthesis analysis was conducted using RHS. FL-LP showed a 2000 fold increase in collagen content, compared to non - encapsulated LP, which resulted in only a 100 fold increase in collagen content in the RHS. The ability of the delivery system to be delivered to the dermis layer was implied in this research work as collagen synthesis by the fibroblasts occurred at the dermal layer. The outcomes in this study suggested that FL-LP was found to be effective in enhancing collagen synthesis in the skin.